Towards a coherent multi-level framework for resource accounting - Leung Pah Hang, M; Martinez-Hernandez, E; Leach, M; Yang, A (Elsevier, 2016)
All rights reserved.With increasing resource scarcity and environmental impacts resulting from inefficient resource utilisation, accounting for resource consumption along the life cycle of a product or service becomes critical for designing production-consumption systems. This work aims at developing a coherent framework for resource accounting to support the evaluation of alternatives for production and consumption activities. The framework provides an understanding of resource utilisation at unit, process, inter-process and production-consumption levels within a system. The multilevel characteristic of this framework allows a comprehensive and holistic view of a system with the potential to reveal how decisions at one level would affect other levels of the system. Based on such a multilevel view, a unique adaptation of the Cumulative Exergy Resource Accounting method is proposed to quantify resource consumption associated with both technological and natural processes. This work also differentiates between and accounts for the operational resource consumption in resource extraction, agriculture and manufacturing and for the capital resource consumption for providing machinery and infrastructure. This is a practical framework for resource accounting that can be used by process engineers and local planners to support decision making regarding alternative system designs, gain insights on the performance of a production system and devise design options including retrofits for improving the overall resource efficiency of a system. By revealing the resource consumption through each system layer, the framework provides a robust and transparent way to capture effects of decision making during design or retrofitting of processes in order to find the most efficient design options. In addition, the framework can be applied to support research in other areas such as those addressing the social, cultural and business perspectives of resource management. Finally, a case study on the production and consumption of sugarcane ethanol is used to illustrate the features of the proposed framework. The framework proved useful in assessing the effects of design decisions at the various levels, such as choosing between molecular sieve and azeotropic distillation at the unit level, adoption of water recycling at the process level, and bagasse exchange flows at inter-process level. The proposed systematic approach has given insights into how changes in resource consumption occur at different levels.